Diversity and ecology of molluscs (Gastropods) in mountain streams, Nurota mountain range, Uzbekistan - JASUR KUDRATOV; ABDUVAEIT PAZILOV; ZOKIR MAXAMMADIYEV; RAʼNO URAZOVA; BEKZOD OTAKULOV; BAXRITDIN BAZAROV; KHUDOYOR KELDIYAROV; ZARINA SOATOVA; XULKAR URINOVA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kudratov J, Pazilov A, Maxammadiyev Z, Urazova R, Otakulov B, Bazarov B, Keldiyarov K, Soatova Z, Urinova X. 2023. Diversity and ecology of molluscs (Gastropods) in mountain streams, Nurota mountain range, Uzbekistan. Biodiversitas 24: 2402-2408. Characterization of the faunal biodiversity of the regions is one of the important tasks in today's era when the influence of the anthropogenic factor has increased, and the natural ecosystems are undergoing drastic changes. Therefore, the faunal composition analysis of molluscs as a part of the natural food chain, the development of measures related to their protection, the disclosure of bioecological features, and the substantiation of scientific solutions are of great scientific and practical importance. This study provides information on the species composition of gastropod molluscs in the streams of the Nurota Mountains of Uzbekistan. Sampling was carried out at 11 stations from April to November 2019. Molluscs include 4 families (Belgrandiellidae, Lymnaeidae, Physidae and Planorbidae), 5 genera, and 15 species. The dominant family in the malacofauna of the study area is Lymnaeidae, one genus and eight species belonging to this family are found in the area. Most molluscs are found on rocky, sandy substrates around plants. This article describes the biological diversity of animals in streams in the Nurota Mountains of Uzbekistan.